PENERAPAN THEORY OF PLANNED BEHAVIOUR DALAM MENJELASKAN PERILAKU KECURANGAN AKADEMIK - Prabawati Putri Handayani, Wahyu (Widya Warta, 2018)
The purpose of this study was to test and to analyze the Theory of Planned Behavior in explaining the behavior of academic cheating at Widya Mandala Catholic University of Madiun. The research variables were moral obligation, attitude, subjective norm, perceived behavioral control, intention to cheat, and academic dishonesty. The samples of the study consisted of 120 undergraduate students of Widya Mandala Catholic University of Madiun. To collect the data, this study used convenience sampling technique and questionnaire. Path Analysis was used to explain the direct and indirect effects among the research variables. This result of the study showed that moral obligation, subjective norm, and perceived behavioral control took effect on intention to cheat. However, attitude did not take effect on intention to cheat. Finally, perceived behavioral control and intention to cheat affected academic dishonesty